The pan-European order at the crossroads: three principles for a new beginning - Kaim, Markus; Maull, Hanns W.; Westphal, Kirsten (2015)
Abstract: The year 2014 confronted European policy-makers with a qualitatively altered situation. For the first time in many years an interstate conflict in Europe - manifested as an inner-state conflict - is being resolved by military means. Persistent uncertainty and a growing potential for conflict are the new realities the European Union (EU) must face - in its eastern neighborhood as well as in the Mediterranean region. This neighborhood also holds major strategic significance for the supply of energy to Europe. In order to limit the risks, it is necessary to define and construct a new pan-European order - based on existing conditions - that can rein in the potential for conflict, ensure greater predictability and build new trust. Germany should use its OSCE chairmanship in 2016 to initiate negotiations to this effect along the lines of new principles, with a view to establishing a pan-European order with a strong energy component as its core. (author's abstract)